2015
DOI: 10.1371/journal.pone.0136995
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Primer with an Inosine Chain at the 5′-Terminus Improves the Reliability of SNP Analysis Using the PCR-Amplified Product Length Polymorphism Method

Abstract: Polymerase chain reaction-amplified product length polymorphism (PCR-APLP) is one of the most convenient and reliable methods for single nucleotide polymorphism (SNP) analysis. This method is based on PCR, but uses allele-specific primers containing SNP sites at the 3′-terminus of each primer. To use this method at least two allele-specific primers and one “counter-primer”, which serves as a common forward or reverse primer of the allele-specific primers, are required. The allele-specific primers have SNP site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Such primers have also been reported to increase the fluorescent signal of real-time PCR [56, 57]. In addition, inosine-flapped APLP primers improve the competitiveness of allele-specific primers to the template DNA, resulting in enhanced reliability of the SNP analysis [33]. The thermodynamics of the primers with inosine flaps has been proven to be less influenced by the sequence of PCR templates than the thermodynamics of the primers with 5′-flaps containing ordinary bases [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such primers have also been reported to increase the fluorescent signal of real-time PCR [56, 57]. In addition, inosine-flapped APLP primers improve the competitiveness of allele-specific primers to the template DNA, resulting in enhanced reliability of the SNP analysis [33]. The thermodynamics of the primers with inosine flaps has been proven to be less influenced by the sequence of PCR templates than the thermodynamics of the primers with 5′-flaps containing ordinary bases [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inosine-flapped APLP primers improve the competitiveness of allele-specific primers to the template DNA, resulting in enhanced reliability of the SNP analysis [33]. The thermodynamics of the primers with inosine flaps has been proven to be less influenced by the sequence of PCR templates than the thermodynamics of the primers with 5′-flaps containing ordinary bases [33]. Furthermore, we reported that our inosine-flapped APLP method in the multiplex SNP analysis showed markedly higher sensitivity than that reported in various studies [61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently developed novel APLP primers with a short inosine extension added to the 5′-terminus. This modification improves the competitiveness of allele-specific primers to the template DNA, resulting in enhanced reliability of the analysis of SNPs [ 28 ]. In the present study, we designed the primers based on this inosine-flapped APLP method.…”
Section: Methodsmentioning
confidence: 99%